Vontade : o métron da hýbris da história da metafísica - Santos, Fábio Candido dos (2015)
The proposal expressed by this work is the defense of the thesis that metaphysics is originally the result of a resentment of the will with the finite and unpredictable mode of Being of life, making it impossible to control and rule the existence and whose summit takes place with the advent of modern philosophy of Descartes and of the cogito as absolute foundation of the reality of the real. Nietzsche identifies this scenario as originating from a change in the essence of the Greco-Roman man who, in modern times, shall be characterized by the rejection of any kind of transcendence to establish himself as the principle and cause of the real. Nietzsche, the Greek world enthusiast, sees this supposed ontological change as establishment of hubris, the Hellenic notion of h bris whose primary sense points to break the man's limit m tron, man's Being - and that is an attempt to equalize or exceed divinity transcendence. In modernity, the h bris settles ontologically in man when the opening of the cogito as an operation of will promotes the death of God. In fact, kill the transcendence and take his place is wanting to be ground when, in fact, is only a means to the ground Being, the truth appear, founding, through man, all that is. Heidegger, another Greek world enthusiast, agrees with Nietzsche, but sees the h bris of the phenomenon more broadly, watching his character history and its connection to what he called a history of Being and its manifestation as metaphysics. The author of Being and Time notes that the will which entails the modern h bris has a Greek origin, more precisely at the time of transition from the pre- Socratic philosophy and metaphysics of Plato and Aristotle. That\'s where Heidegger says the change of attitude in the Being of man identified by Nietzsche in modernity takes shape. The birth of metaphysics is the end of ontological agreement between man and ph sis Being for the establishment of Eros for knowledge, or philosophy. This desire is the will that will establish the will which will promote the death of God and the establishment of man as the real measure, ie, the h bris of modern man. Heidegger finds the origin of this event and its entire historical development the nihilism that Nietzsche saw only in modernity. As a result of crystallization of contemporary rampant posture of man, Heidegger points out the appearance of technique and its ambiguous nature, which can be both a threat to the Being of man to equalize the way in which being is shown from it as a possibility of "new beginning" for humanity. The itinerary, mediated by Heidegger and Nietzsche, of the establishment of the ancient metaphysics as principle of h bris to its heyday in modernity as the death of God, and its unfolding as a technique, it is the task of the following work.